Pengaruh Orientasi Pelanggan, Orientasi Kewirausahaan, dan Lingkungan Industri Terhadap Kinerja Pemasaran Syariah Melalui Keunggulan Bersaing Pada UMKM Olahan Pangan Seafood di Kabupaten Sidoarjo - Christian, Tristan Jason; Yoestini, Yoestini (Jurnal Ilmiah Ekonomi Islam, 2023)
Marketing performance is an assessment of how the marketing strategy implemented by the company is realized. With the marketing performance assessment, it can be seen how far the company has developed. The aim of this research is to examine the mediating effect of competitive advantage in the influence of customer orientation, entrepreneurial orientation, and industrial environment on marketing performance in Seafood Processed MSMEs in Sidoarjo Regency. The population in this study was 140 Seafood Processing MSMEs in Sidoarjo Regency. The sampling method used the Slovin method, numbering 104 and data was taken using the accidental sampling method. Data collection techniques use questionnaires and observation methods. The data analysis method uses multiple linear regression with a path analysis approach and the SPSS program. The research results show that customer orientation, entrepreneurial orientation, and the industrial environment have a positive and significant influence on marketing performance through competitive advantage. The competitive advantage variable is proven to be an intervening variable. The results of the path analysis test show that competitive advantage can mediate the influence of customer orientation, entrepreneurial orientation, and industrial environment and provide a significant and positive influence on marketing performance. Seafood Processed MSMEs in Sidoarjo Regency are advised to improve these factors to improve marketing performance.